Absorção capilar e resistividade elétrica de concretos compostos com cinza de casca de arroz de diferentes teores de carbono grafítico - Mostardeiro Neto, Carlos Zinn (2011)
There are constant searches for alternatives to reduce the environmental impact in the production of in consumables, like concrete, that is actually a pollutant. Mineral additions have been investigated as partial substitutions for cement in concrete because other than taking advantage of industrial residues, that many times don t have a specific distinction and are degrading in the ambiental view, they can offer better material durability characteristics, as proved in previous studies. In Brazil, a big rice producer, millions of tons of rice husk are produced, where part is utilized for energy production in thermoelectric plants. The rice husk ash, result of the burning of the husk, has been the font of studies as a partial substitution of cement in concrete. There are still very few studies that make a comparison of the viability influence of the utilization of rice husk ash with different levels of carbon graphitic (light and dark grey), obtained by controlled burnings, a durable characteristic in concretes. In this work, mixtures containing different levels of light and dark RHA were investigated in concrete structural performance through water capillary absorption, following the NBR 9779:1995 and apparent electrical resistivity, conforming to the four electrode method (Wenner). Additionally, an analysis was made of the axial compressive strength in accordance with the NBR 5739:2007. For this, eight compound mixtures were tested and investigated in relation to their w/wc 0,35, 0,50 e 0,65: one composited of 100% Portland cement, REF, three with substitution of cement by light RHA in levels of 10%, 20% and 30%, namely 10 LRHA, 20 LRHA, 30 LRHA, respectively, and another three with the same levels of dark RHA replace cement, identified as 10 DRHA, 20 DRHA and 30 DRHA, respectively, and a mixture with 10% of silica fume, 10 SF, to compare results. The increase in cure time and in the purport of the substitution of cement by RHA resulted in better performance as to the investigated properties. In equality of w/wc relations, the compressive strength values were, in general, similar, indifferent to the level of carbon graphitic of the RHA. The composite mixture with DRHA presented better performance with regards to capillary absorption, even though it was overcome by the mixture with SF. In relation to electrical resistivity, the composed mixture of 30% LRHA presented better performance in all analysis times.